The Principle of Subsidiarity as a Social and Political Principle in Catholic Social Teaching - Evans, Michelle (University of Notre Dame Australia, Centre for Faith Ethics and Society, 2013)
The principle of subsidiarity is a multi-layered and flexible principle that can be utilised to empower, inform,enhance and reform scholarship in a range of significant areas, however, it has been somewhat overlooked inrecent scholarship. In order to highlight the continued relevance and potential applications of the principle,this, the first of two papers, will provide a detailed analysis of the meaning and application of the principle ofsubsidiarity in Catholic social teaching. In doing so, the interplay of the principle of subsidiarity and other keyprinciples of catholic social teaching such as dignity of the person, solidarity, and the common good will behighlighted. The second part of this paper discusses the political applications of the principle, including itsability to inform scholarship on the allocation of governmental powers (including federalism), democracy,and individual participation in government. This leads to a discussion in the second paper, of the Catholicaspects of subsidiarity in the governance of the European Union.